Dampak reporter and nonreporter company dividend terhadap kandungan informasi dan transfer informasi intra industri (Studi kelompok perusahaan manufaktur BEI periode 2009-2011) - Apriani, Elfika; DP, Emrinaldi Nur; Hanif, Rheny Afriana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The purpose of the research was to investigate the information content and intra industry effect of dividend announcement. The analysis include four aspects: information content, risk (beta), intra industry effect of dividen by big and small size firms, and impact firm characteristics to abnormal return nonreporter firm.The analysis for information content, risk (beta), intra industry effect used event study and for impact of firm characteristics used multiple linier regression.Result of this research showed that there was information content around the date of dividend announcement, but there was no difference between abnormal return by big and small size firms. The difference between beta before and after dividend announcement is not significant. The difference between beta big size firms and small size firms after dividend announcement is not significant. The intra industry effect of dividend announcement showed abnormal return with two effects: competitive effect and contagion effect. The firm specific characteristics used in this research was not significant to explain the fenomena intra industry.Keywords: dividend, information content, intra industry effect, competitice effects and contagion effects.